High serum amyloid A predicts risk of cognitive impairment after lacunar infarction: Development and validation of a nomogram - Ye, Sheng; Pan, Huiqing; Li, Weijia; Wang, Bing; Xing, Jingjing; Xu, Li (Frontiers in Neurology, 2022)
Background: Post-stroke cognitive impairment (PSCI) after lacunar infarction was worth attention in recent years. An easy-to-use score model to predict the risk of PSCI was rare. This study aimed to explore the association between the serum amyloid A (SAA) and cognitive impairment, and also developed a nomogram for predicting the risk of PSCI in lacunar infarction patients. Methods: A total of 313 patients with lacunar infarction were enrolled in this retrospective study between January 2021 and December 2021. They were divided into a training set and a validation set at 70%:30% randomly. The Chinese version of the Mini-mental State Examination (MMSE) was performed to identify cognitive impairment after three months after discharge. Univariate and multivariate logistic regression was used to determine the independent risk factors for PSCI in the training set. A nomogram was developed based on the five variables, and the calibration curve and the receiver operating characteristic (ROC) curve were drawn to assess the predictive ability of the nomogram between the training set and the validation set. The decision curve analysis (DCA) was also conducted in both two sets. Results: 52/313 (16.61%) participants were identified with PSCI. The serum amyloid A levels in patients with PSCI were significantly higher than non-PSCI patients in the training set (P<0.001). After multivariate analysis, age, diabetes mellitus, white blood count, cystatin C, and serum amyloid A were independent risk predictors of PSCI. The nomogram demonstrated a good discrimination performance between the training set (AUC=0.860) and the validation set (AUC=0.811). The DCA showed that the nomogram had a well clinical utility in the two sets. Conclusions: The increased serum amyloid A is associated with PSCI in lacunar infarction patients, and the nomogram developed with serum amyloid A can increase prognostic information for the early detection of PSCI.